The Effect of Endogenous Angiotensin II on Alveolar Fluid Clearance in Rats with Acute Lung Injury - Jia Deng; Dao-xin Wang; Wang Deng; Chang-yi Li; Jin Tong (Canadian Respiratory Journal)
BACKGROUND: In acute lung injury (ALI), angiotensin II (Ang II) plays a vital role in the stimulation of pulmonary permeability edema formation through the angiotensin type 1 (AT1) receptor. The effect of Ang II on alveolar fluid clearance (AFC) in ALI remains unknown.